cAMP signaling pathway controls glycogen metabolism in Neurospora crassa by regulating the glycogen synthase gene expression and phosphorylation - Freitas, Fernanda Zanolli [UNESP]; de Paula, Renato Magalhaes [UNESP]; Bertucci Barbosa, Luiz Carlos [UNESP]; Terenzi, Hector Francisco; Bertolini, Maria Celia [UNESP] (Academic Press Inc. Elsevier B.V., 2010)
The cAMP-PKA signaling pathway plays an important role in many biological processes including glycogen metabolism. In this work we investigated its role in the Neurospora crassa glycogen metabolism control using mutant strains affected in components of the pathway, the cr-1 strain deficient in adenylyl cyclase activity therefore has the PKA pathway not active, and the mcb strain a temperature-sensitive mutant defective in the regulatory subunit of PKA therefore is a strain with constitutively active PKA. We analyzed the expression of the gene encoding glycogen synthase (gsn), the regulatory enzyme in glycogen synthesis as a potential target of the regulation. The cr-1 strain accumulated, during vegetative growth, glycogen levels much higher than the wild type strain indicating a role of the PKA pathway in the glycogen accumulation. The gsn transcript was not increased in this strain but the GSN protein was less phosphorylated "in vitro", and therefore more active, suggesting that the post-translational modification of GSN is likely the main mechanism controlling glycogen accumulation during vegetative growth. Heat shock down-regulates gsn gene transcription in the two mutant strains, as well as in the wild type strain, suggesting that the PKA pathway may not be the only pathway having a direct role in gsn transcription under heat shock. DNA-protein complexes were formed between the STRE motif in the gsn promoter and nuclear proteins from heat-shocked mycelium. However STRE was not able to induce transcription of a reporter gene in Saccharomyces cerevisiae, suggesting that the motif might be involved in a different way of regulation in the N. crassa gene expression under heat shock. The CRE-like DNA elements present in the gsn promoter were shown to be bound by different proteins from the PKA mutant strains. The DNA-protein complexes were observed with proteins from the strains grown under normal condition and under heat shock indicating the functionality of this DNA element. In this work we presented some evidences that the PKA signaling pathway regulates glycogen metabolism in N. crassa in a different way when compared to the well-characterized model of regulation existent in S. cerevisiae. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: cAMP-PKA signaling pathway; Gene expression; STRE; CRE; DNA shift; Protein phosphorylation